Information and Communication Technologies for the Higher Education: A Bibliographic Review - Torres Mirez, Karl Friederick; Alarcón Llontop, Luis Rolando (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Information and Communication Technologies (ICT) are increasingly integrated into educational processes, including those at the university level, transforming them. Using a literature review methodological approach, this study explores research extracted from Scopus, focused on the use of ICT in university higher education. Manual coding was applied to the bibliometric data obtained and reinforced with the use of artificial intelligence (AI) GPT-4 and VOSviewer software. The central research question was: what are the researches on ICT in the university context in their numbers, origins and main topics?